Zero-correlation zone complementary sets based on iteration - LI Yu-bo; XU Cheng-qian (Tongxin xuebao)
Based on orthogonal matrices and interleaving iteration,two constructions of zero correlation zone comple-mentary（Z-complementary） sets were presented.The Z-complementary sets proposed not only have ideal auto-correlation and cross-correlation in a zone,but also have larger set sizes compared with the conventional comple-mentary sets.Moreover,their set sizes can achieve the theoretical bound.